Localizing Jihad, Globalizing Jimat: Banser and Jamaah Maiyah in a Global Village - Karim, Ahmad (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
During the last two decades, a dramatic transition from authoritarianism to a rapid process of democratization has been experienced by many different societies across the world. In Indonesia, reformasi 1998 has not only been followed by a massive transformation in many different dimensions but also the changing character of interdependently hybrid governance arrangements which lead to an ?authoritarian turn?, particularly concerning about the visions of social harmony within a post-democratization context that is impacted by religious violent extremism. As such extremism is experienced daily in Indonesia and elsewhere in the world, while there is an absence of effective state interventions or at least the fact that state is no longer perceived as the principle referent for security, there has been an exceptional trend of what I call ?ref-ormas-i'. It indicates how non-state actors, more specifically Ormas (mass organizations) is taking the shape of providing people?s basic needs, professing security, promoting inter-religious tolerance, and even campaigning nationalism in the local, national, and global communities. This phenomenon certainly raises a question of how the non-state actors organize their role ?acting like a state? in society to produce new forms of ?imagined communities?. Based on ethnographic fieldwork in two different Indonesian urban settings in Surabaya and Yogyakarta, this paper focuses on elaborating the roles of two different moderate Islamic groups, Banser and Jamaah Maiyah, more specifically on the discourses they use and the empirical actions they perform in securing the local community, defending the national ideology, and idealizing the global harmony through different interpretation of jihad and different approach of engagement in the society, more specifically for responding wide-spread religious extremism.